Bank competition and financing efficiency under asymmetric information - Biswas, Swarnava (Sonny); Koufopoulos, Kostas (Journal of Corporate Finance, 2020)
We consider a setting in which an entrepreneur seeks bank financing, and the project type is her private information. Different from existing theories featuring information asymmetry, and consistent with empirical findings, our model predicts: greater bank competition leads to increased bank lending as interest rates fall, leading to lower quality loans. The relationship between market power and financing efficiency is hill-shaped. An intermediate level of market power is desirable, as it can mitigate inefficiencies arising due to cross-subsidization among borrowers in a pooling equilibrium. Interest rate controls may achieve efficiency, but the specific policy depends on the bank market structure.